Panama : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Panama. (IMF Staff Country Reports; Country Report ;, 2021)
After over two decades of unprecedented economic expansion, Panama's economy contracted sharply in 2020 amidst challenges from the COVID-19 pandemic. As conditions rapidly deteriorated, Panama requested financial support under the Rapid Financing Instrument (RFI) for 100 percent of quota equivalent to USD 0.5 billion (SDR 0.4 billion) to address immediate balance of payments needs, which the IMF Executive Board approved on April 15, 2020. Subsequently, uncertainties magnified, and Panama requested a two-year arrangement under the Precautionary and Liquidity Line (PLL) for 500 percent of quota, equivalent to USD 2.7 billion (SDR 1.9 billion), as insurance against extreme external shocks, which was approved by the IMF Executive Board on January 19, 2021.